2021
DOI: 10.3389/fpubh.2020.620023
|View full text |Cite
|
Sign up to set email alerts
|

The Combined Impact of Gender and Age on Post-traumatic Stress Symptoms, Depression, and Insomnia During COVID-19 Outbreak in China

Abstract: The mental health problems might have been increased owing to the COVID-19 pandemic with the commencement of the year 2020, therefore, an epidemiological survey appraising the burden of mental health issues among the general population is imperative. This cross-sectional study attempts to reveal the underlying mental health conditions, such as Post-Traumatic Stress Symptoms (PTSS), depression, and insomnia, relating to the pandemic situation, and to further examine the combined effects of gender and age on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
37
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 61 publications
(85 reference statements)
7
37
1
Order By: Relevance
“…At the same time, compared with other occupations, medical staff had higher depressive symptoms during the epidemic ( 51 ). Furthermore, another study found that pre-psychological problems, post-psychological problems, 2-week illness were significantly associated with higher depressive symptoms ( 52 ). Finally, Wuhan exposure, media exposure, ethnicity, religion, and living arrangement were also considered in the previous studies ( 52 , 53 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…At the same time, compared with other occupations, medical staff had higher depressive symptoms during the epidemic ( 51 ). Furthermore, another study found that pre-psychological problems, post-psychological problems, 2-week illness were significantly associated with higher depressive symptoms ( 52 ). Finally, Wuhan exposure, media exposure, ethnicity, religion, and living arrangement were also considered in the previous studies ( 52 , 53 ).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, another study found that pre-psychological problems, post-psychological problems, 2-week illness were significantly associated with higher depressive symptoms (52). Finally, Wuhan exposure, media exposure, ethnicity, religion, and living arrangement were also considered in the previous studies (52,53). Therefore, these variables were included in this study because they had been examined in previous related studies (49)(50)(51)(52)(53).…”
Section: Demographic and Socioeconomic Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…The Corona Virus Disease 2019 (COVID-19) pandemic broke out suddenly at the beginning of 2020 in Wuhan, China and quickly spread across the whole country and other parts of the world (Chen et al, 2020(Chen et al, , 2021Dan, 2020;Li and Xu, 2020). Due to its highly contagious nature and unavailable treatment drugs, the public had to face a long period time of home quarantine, which not only increased the sensitivity of the general public to the new pandemic, but also posed a serious threat to people's mental health (Dan, 2020;Liu, 2020;Liu et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Thirdly, at present, Chinese pandemic prevention and control was relatively stable, but the existence of imported cases and the safety problems of imported food will also cause stress on domestic public [18,19]. Lastly, many people exhibit compulsive checking and reassurance seeking regarding possible pandemic-related threats or experience traumatic stress symptoms, such as frequent nightmares and intrusive thinking [16, [20][21][22]. People's exposure to stress is associated with decreased sleep quality, while people with higher perceived stress tend to have lower sleep quality.…”
Section: Introductionmentioning
confidence: 99%